1977
DOI: 10.1002/ccd.1810030305
|View full text |Cite
|
Sign up to set email alerts
|

A geometric basis for calculation of right ventricular volume in man

Abstract: A clinically applicable method for determining right ventricular volume was developed using a new hemlelllptlcal model. The model was derived from a detailed study of right ventricular geometry. Silicone rubber casts were made from 7 adult human right ventricles at autopsy. Cast volumes measured by water displacement ranged from 30 to 144 ml. Serial sections were made of each cast, and the product of the long and short axis of all sections was found to be directly related to the cross-sectional area and Indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The most suitable BiPL position for volume calculation, however, seem to be the 30" RAOJ60" LAO because the greatest accuracy is achieved when in one of the projections (ie, 30" RAO) the cast displays the largest possible area to the X-ray beams [6]. The smallest errors in RVV occurs in these BiPL views [5,35], and our findings confirm this.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The most suitable BiPL position for volume calculation, however, seem to be the 30" RAOJ60" LAO because the greatest accuracy is achieved when in one of the projections (ie, 30" RAO) the cast displays the largest possible area to the X-ray beams [6]. The smallest errors in RVV occurs in these BiPL views [5,35], and our findings confirm this.…”
Section: Discussionsupporting
confidence: 71%
“…Our cast studies showed that in addition to the established BiPL PA/LAT and RAOI LAO right ventricular volumetric methods [2][3][4][5][6][7]35,36] the BiPL calculations in the two axial projections [long axial and HCL) also gave very good correlations. Consequently, in patients studied for ventricular septa1 defects, endocardia1 cushion defects, D-transposition of the great arteries, etc, RVV may be obtained from these newer angiographic projections without the need for additional "standard" contrast studies.…”
Section: Discussionmentioning
confidence: 81%
“…Diagnoses of biopsy specimens were not different in the group with pacemakers compared with the group that did not have pacemakers. From the 12 patients who did not have pacemakers, one biopsy specimen was normal, six indicated nonspecific myopathic changes, one indicated small-vessel disease, two indicated arrhythmogenic right ventricular dysplasia, and two indicated myocarditis (neither patient with myocarditis had previous intracardiac instrumentation). Of the six patients with pacemakers at the time of biopsy, three had nonspecific myopathic changes, one had small-vessel disease, one had myocarditis, and one had normal biopsy specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Because the geometry of the right ventricle is rather complex and variable, it is difficult to calculate reliable volumes from these projections. Many geometric models based on different projections have been proposed for volumetry of right ventricles in the past [1][2][3][4][5][6][7]. These models have been validated decades ago often in small samples.…”
Section: Introductionmentioning
confidence: 99%